Pengaruh Cyberloafing dan Leader Member Exchange terhadap Innovative Work Behavior Pada Karyawan Perum Jasa Tirta II - Dedeng Abdul Gani Amruloh; Wahyu Yulianto Wahyu; Annisa Resyanti Wulandari (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The background of this research is that there are still many employees of Perum Jasa Tirta II who have not been able to provide brilliant ideas into the operational performance of the company. This can be seen because there are several work processes that are less effective and efficient, therefore it is very important for Perum Jasa Tirta II to further improve Innovative Work Behavior. From a total of 947 employees, it is estimated that only some employees have developed their innovations, then the results of the innovation development of some of these employees resulted in 14 applications and service websites that have been implemented at Perum Jasa Tirta II from the standard number of applications and which should be 26. This research using a quantitative research model, data were collected using a questionnaire technique with 90 respondents, the test method used IBM SPSS 26. The results showed that Cyberloafing had a significant negative effect on Innovation Work Behavior in Perum Jasa Tirta II employees and Leader Member Exchange had a significant positive influence significant effect on Innovation Work Behavior among employees of Perum Jasa Tirta II.